2021
DOI: 10.1186/s13075-021-02502-1
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of osteoarthritis in the rat with an antibody specific to type II collagen modified by reactive oxygen species

Abstract: Background Osteoarthritis (OA) is a disease of the whole joint, with articular cartilage breakdown as a major characteristic. Inflammatory mediators, proteases, and oxidants produced by chondrocytes are known to be responsible for driving cartilage degradation. Nevertheless, the early pathogenic events are still unclear. To investigate this, we employed an antibody that is specific to oxidative post-translationally modified collagen type II (anti-oxPTM-CII) to detect early cartilage pathogenic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the present study, a typical joint broadening symptom was observed after DMM surgery that peaked during week 1, persisted until the end of the study, and was sensitive to anti-inflammatory Zilretta treatment. Joint broadening can potentially be a consequence of surgery, synovitis, bone remodeling or another pathology [ 16 , 20 ]. The effect has been shown to be exaggerated when rats are housed in RCCs compared with type IV cages [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a typical joint broadening symptom was observed after DMM surgery that peaked during week 1, persisted until the end of the study, and was sensitive to anti-inflammatory Zilretta treatment. Joint broadening can potentially be a consequence of surgery, synovitis, bone remodeling or another pathology [ 16 , 20 ]. The effect has been shown to be exaggerated when rats are housed in RCCs compared with type IV cages [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Materials Chemistry B mobility of the animals, with the outcome being similar to that observed in post-traumatic human OA. 61,[80][81][82][83] Studies have shown that the ACLT model exhibits changes in the cartilage and the underlying bone at the early stages of ligament transection. 62,81,82,84,85 The efficacy of the BI-4394 loaded hydrogel to prevent cartilage degradation through MMP-13 blocking was evaluated in an in vivo model.…”
Section: Papermentioning
confidence: 99%
“…61,[80][81][82][83] Studies have shown that the ACLT model exhibits changes in the cartilage and the underlying bone at the early stages of ligament transection. 62,81,82,84,85 The efficacy of the BI-4394 loaded hydrogel to prevent cartilage degradation through MMP-13 blocking was evaluated in an in vivo model. Post ACLT, the test animals were implanted with Gel@10 as a single dose (SD) or a double dose (DD) through IA administration, to determine the effective dose for therapeutic efficacy.…”
Section: Papermentioning
confidence: 99%